Induced pemphigus erythematosus after treatment for plaque psoriasis with secukinumab: a case report - Hu, Fengming; Peng, Hong; Gong, Jian; Tao, Xiaohua; Wang, Xi; Bao, Jianwei; He, Pingxiu; Dirwanto, Lismin; Liu, Mingqiang; Yang, Hongbing (Frontiers in Immunology, 2025)
Secukinumab is a fully human monoclonal antibody that specifically targets and neutralizes interleukin (IL)-17A, a cytokine typically involved in the mucocutaneous defense against pathogens. Despite its favorable safety profile, serious adverse events such as inflammatory bowel disease, oral pemphigoid-like lesions, and lupus erythematosus have been reported. While widely used for psoriasis treatment, cytokine-based therapies carry a potential risk of triggering autoimmune responses. The precise mechanism by which secukinumab induces pemphigus erythematosus remains unclear but may involve immune dysregulation, autoantibody production, microbiota influences, and genetic susceptibility. We report a case of pemphigus erythematosus occurring in a psoriasis patient during secukinumab therapy, which improved after treatment with methylprednisolone sodium succinate injection, leading to clinical symptom resolution. Clinicians should remain vigilant for potential complications and develop individualized management strategies for patients receiving secukinumab.